Botulinum Toxin Injection Techniques for the Management of Adult Spasticity. Issue 4 (8th October 2014) - Walker, Heather W.; Lee, Michael Y.; Bahroo, Laxman B.; Hedera, Peter; Charles, David
Abstract: Spasticity is often experienced by individuals with injury or illness of the central nervous system from etiologies such as stroke, spinal cord injury, brain injury, multiple sclerosis, or other neurologic conditions. Although spasticity may provide benefits in some patients, it more often leads to complications negatively impacting the patient. Nonpharmacologic treatment options often do not provide long‐term reduction of spasticity, and systemic interventions, such as oral medications, can have intolerable side effects. The use of botulinum neurotoxin injections is one option for management of focal spasticity. Several localization techniques are available to physicians that allow for identification of the selected target muscles. These methods include anatomic localization in isolation or in conjunction with electromyography guidance, electrical stimulation guidance, or ultrasound guidance. This article will focus on further description of each of these techniques in relation to the treatment of adult spasticity and will discuss the advantages and disadvantages of each technique, as well as review the literature comparing the techniques.